2004
DOI: 10.1136/ard.2003.014233
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of radiological outcome in early rheumatoid arthritis in clinical practice: role of antibodies to citrullinated peptides (anti-CCP)

Abstract: Objective: To investigate the role of anti-cyclic citrullinated peptide antibody (anti-CCP) for the prediction of radiological outcome in patients with early rheumatoid arthritis. Methods: Anti-CCP was assessed at baseline in 379 patients with early rheumatoid arthritis (disease duration ,1 year). Radiological joint damage and progression were assessed by Larsen score after two years of follow up (end point) and used as outcome variables. The prognostic value of anti-CCP and other demographic and disease relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

23
257
7
11

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 382 publications
(302 citation statements)
references
References 28 publications
23
257
7
11
Order By: Relevance
“…Kuhn et al, for example, recently demonstrated that administration of anti-citrullinated fibrinogen antibodies enhanced disease severity in an experimental mouse model of arthritis (4). In the majority of patients with RA, the presence of ACPAs antedates disease onset (5,6), and ACPA-positive patients present with a more severe and erosive form of arthritis (7)(8)(9)(10)(11)(12)(13)(14)(15)(16). A commercial enzyme-linked immunosorbent assay (ELISA) based on cyclic citrullinated peptides (CCPs) detects ACPAs and is now routinely used in the diagnosis of RA.…”
mentioning
confidence: 99%
“…Kuhn et al, for example, recently demonstrated that administration of anti-citrullinated fibrinogen antibodies enhanced disease severity in an experimental mouse model of arthritis (4). In the majority of patients with RA, the presence of ACPAs antedates disease onset (5,6), and ACPA-positive patients present with a more severe and erosive form of arthritis (7)(8)(9)(10)(11)(12)(13)(14)(15)(16). A commercial enzyme-linked immunosorbent assay (ELISA) based on cyclic citrullinated peptides (CCPs) detects ACPAs and is now routinely used in the diagnosis of RA.…”
mentioning
confidence: 99%
“…Several studies have shown that radiological outcome can be predicted by the presence of RF [19,20] and antibodies against cyclic citrullinated peptides (anti-CCP) [21][22][23] at the time of diagnosis of early RA, and the level of anti-CCP seems to be of importance [24]. In an inception cohort of patients with newly presenting inflammatory poly-arthritis [19], inflammatory activity [joint counts and C-reactive protein (CRP)] and immune pathology (RF and RN) predicted the severity of erosions early in the disease.…”
Section: Introductionmentioning
confidence: 99%
“…We measured binding of native and citrullinated forms of vimentin [66][67][68][69][70][71][72][73][74][75][76][77][78] and a-enolase [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] and noncitrullinated type II collagen [258][259][260][261][262][263][264][265][266][267][268][269][270][271][272] to 88 class II alleles on Luminex beads (which includes alleles of many varying degrees of susceptibility and resistance). We expressed DRB1*04:01, *04:02, and *08:01 in T2 cells and mutated DRB1*04:01 at positions 67, 70, 71, 74, and 86 to corresponding residues in DRB1*04:02, *04:03, *04:04, *04:05, and *08:01.…”
mentioning
confidence: 99%